Pertanggungjawaban Pidana Terhadap Pelaku Pembunuhan Pada Anak - I Made Wisnu Adi Jaya; Erlina Bachri; Yulia Hesti (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Literally, children are a mandate as well as a gift from God Almighty, even children are considered the most valuable wealth compared to other property assets. Therefore children as a mandate from God must always be guarded and protected because in children inherent dignity and rights as human beings which must be upheld, but crimes are increasingly occurring regardless of who the object is. Indonesia has laws to protect children in the legal context of perpetrators who commit crimes against minors. The purpose of this research is to analyze the arrangement of criminal responsibility for the perpetrators of the murder of minors.